Ultrafast photoconductivity dynamics in narrow-gap HgCdTe films - N. B. Refvik; D. N. Purschke; C. E. Jensen; W. Pan; H. R. J. Simpson; W. Lei; R. Gu; J. Antoszewski; G. A. Umana-Membreno; L. Faraone; F. A. Hegmann (APL Materials)
Mercury cadmium telluride (Hg1−xCdxTe or MCT) is the premier material for infrared detection. However, despite its importance, studies exploring the ultrafast photoresponse in this semiconductor alloy are limited. Here, we use time-resolved terahertz spectroscopy to perform a detailed study of the picosecond charge carrier dynamics in long-wave infrared Hg1−xCdxTe (x ∼ 0.2) films, providing insight into ultrafast carrier cooling and temperature-dependent scattering mechanisms. Due to the multilayer photoexcited sample geometry, an elementary thin-film analysis leads to a negative photoconductivity artifact. We, therefore, derive a modified thin-film photoconductivity formula to accurately extract a Drude photoconductivity spectrum. In our analysis, we include the effects of carrier diffusion and the conduction band non-parabolicity in Hg1−xCdxTe. We extract ultrahigh electron mobilities as large as 6 × 105 cm2 V−1 s−1 at 25 K. At cryogenic temperatures, we find the photoexcited electron mobility is up to four times larger than the dark mobility, which we attribute to suppression of ionized impurity scattering due to hole capture by acceptor-type Hg vacancies. In addition, after photoexcitation, we observe a relatively slow rise in photoconductivity over a 10 ps timescale with a monotonically increasing carrier scattering time and a carrier effective mass that decays exponentially with a time constant of 1.9 ps, which we attribute to hot-carrier cooling dynamics in the non-parabolic conduction band.